1998
DOI: 10.2214/ajr.171.2.9694471
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and portal vein flow pattern in correlation with intrahepatic fat deposition and liver histology in patients with chronic hepatitis C.

Abstract: OBJECTIVE.The flow pattern in hepatic veins depends on cardiac physiology and liver histology. The aim of our study was to determine the dependence of the flow pattern of he patic and portal veins in relation to histologic features in patients with chronic hepatitis C. SUBJECTS AND METHODS.In 135 patients with chronic hepatitis C, the Doppler sonography spectrum of the right hepatic vein was classified as triphasic, biphasic, or monophasic. The flow of theportalvein wascharacterizedaccordingto theundulation(ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
1
17

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(140 citation statements)
references
References 16 publications
10
112
1
17
Order By: Relevance
“…The relative contributions of intrahepatic fat deposition and inflammatory changes to the flow patterns of the hepatic and portal veins are unknown (Dietrich et al 1998). The main finding of this study is that the VPI, MFV, V max , and V min decrease in patients with fatty liver.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The relative contributions of intrahepatic fat deposition and inflammatory changes to the flow patterns of the hepatic and portal veins are unknown (Dietrich et al 1998). The main finding of this study is that the VPI, MFV, V max , and V min decrease in patients with fatty liver.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have shown that the flow of the hepatic and portal veins is altered in patients with liver cirrhosis, portal vein thrombosis, Budd-Chiari syndrome, and vascular malformations (Dietrich et al 1998;Bargallo et al 2006;Bolognesi et al 2007). However, a recent study with a similar design has been published showing the relationship between fatty infiltration of the liver and decreased portal venous velocity and pulsatility (Balci et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Table 3 presents results of the imaging techniques used in diagnosis of NAFLD-NASH. 86,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The underlying physical principle of imaging techniques are the same between adults and children. Consequently research in both age groups could be used to approve the use of these methods in pediatric field.…”
Section: Image Studiesmentioning
confidence: 99%
“…91 The hepatic and portal vein flow pattern is correlated with fatty infiltration, and occasionally with inflammation and fibrosis. 13,92,93 US of the liver is a safe and repeatable imaging technique. It should be part of the routine health examination of obese adolescents.…”
Section: Ultrasonography (Us)mentioning
confidence: 99%